Expanding the students' vocabulary by using musical flashcards at kindergarten school - Salma Hira; Siti Ngaisah; Ekka Zahra Puspita Dewi; Febry Wulandari; Nabila Fateha; Ana Safitri (Patria Educational Journal (PEJ), 2025)
Kindergarten learners frequently faced challenges in retaining vocabulary due to repetitive learning tasks, necessitating prompt measures to enhance classroom techniques. This research wanted to boost vocabulary proficiency among kindergarten students by utilizing "Musical Flashcards." The study applied a Classroom Action Research (CAR) framework, executed over 2 cycles. Every cycle included four key stages: planning, acting, observing, and reflecting. The subjects of the study consisted of 25 kindergarten pupils from RA Mambaul Ulum Bono Data were gathered through qualitative methods and quantitative methods. The results indicate that using Musical Flashcards effectively improved the classroom environment and enriched students' vocabulary. During Cycle I, merely 55 % of students achieved the vocabulary mastery, mainly because of difficulties in classroom management. Following the adjustments to the musical rhythm and card interaction in Cycle II, the proportion of students attaining mastery rose notably to 80%. The multi-sensory method successfully enhanced engagement, visual recall, and pronunciation precision. In summary, Classroom Action Research using Musical Flashcards effectively addressed vocabulary retention challenges and enhanced the quality of teaching and learning in early childhood education.